Transient model to predict the performance of thermoelectric generators coupled with solar pond. (15th May 2016) - Ding, L.C.; Akbarzadeh, A.; Date, A.
Abstract: Solar pond has been a reliable supply of heat source for industrial process that requires heat at the temperature <100 °C. In this paper, the prospect of solar pond in generating electricity has been explored with the aid of using TEGs (thermoelectric generators) for converting the heat available at LCZ (lower convective zone) into electricity. By using the transient heat transfer model developed and the testing result of a thermoelectric module, this study has covered the potential of generating electricity for the solar pond operates in the climate of Group A, B, and C under Köppen climate classification. The effect of heat extraction, climatic variation, temperature polarisation, and the conversion efficiency of TEG on the thermal performance and electrical performance of the system has been discussed. The solar pond operates in Riyadh (Group B of Köppen climate classification) possesses the highest potential in generating electricity, which is about 4.834 kWh/year-m 2 at heat extraction of 15% of year average horizontal solar radiation (i.e. solar pond yearly efficiency of 15%) while having average LCZ temperature of 80 °C throughout the year. Overall, the thermal-electrical conversion efficiency, η t of this system is in the range of 1%–1.5% from the heat extracted. Highlights: The electric power generation from solar pond using TEGs is analysed. The numerical result is compared with a commissioned commercial 500 m 2 solar pond. The method presented has a high scalability for further analysis in the future.